Rereading of The Sabbath Law (Exodus 20: 8-11) as A Response to Modern Slavery Issue - Yohanes Rahdianto Suprandono; Robert Setio (Jurnal Jaffray, 2021)
This research was motivated by concerns about the problem of modern slavery. The author will interpret Exodus 20:8-11 on the Sabbath to respond to the issue of slavery. The method of interpretation that will be used is deconstruction and social criticism. The use of the social criticism method sees the text as a practice of discourse that is ideologically charged and has specific interests. The text is not neutral but rather is advocating. In the text itself, two social groups conflict with each other. The interpretation of the existing Sabbath is interpreted normatively, legalistically, ritualistically, sociologically, theologically and eschatologically. The results of reinterpreting the Sabbath using a deconstructive method show that the Sabbath has been abolished because every day is interpreted as a forced workday. Forced labour is driven by fear and worry. The Sabbath was forgotten for political and economic motives. The Sabbath was abolished because time was money, so people were traded and enslaved for the sake of making money. The reinterpretation of the Sabbath text with the method of social criticism finds the theological meaning of the Sabbath. The God of the Sabbath is described as the forerunner of the liberation of slavery throughout the ages. God’s Sabbath-keeping people today have a liberation mission to help people who are victims of modern slavery.